KORELASI ANTARA BUDAYA ORGANISASI DENGAN KOMUNIKASI ORGANISASI DI MTSN 1 BONE - Akram Akram; Susdiyanto Susdiyanto; Muhammad Yaumi (Universitas Islam Negeri Alauddin Makassar, 2019)
This study aims to: 1)describe the reality of organizational culture; 2)describe the reality of organizational communication; and 3)examine the correlation between organizational culture and organizational communication at Madrasah Tsanawiyah(Islamic Middle School) 1 Bone. This research uses quantitative methodology with correlational design to explain the research questions. The instrument used to measure the variabels of this study was a questionnaire then analyzed with descriptive statistics and inferntial statistics use analiysis of the product moment with SPSS version 21 software. The result of the study show in descriptive of organizational culture is in the very conducive category of 86,38% and organizational communication is in the good category of 83,05%. In addition, the analysis of inferential with correlation product moment analysis suggest that there is a positive and significant correlation between organizational culture and work climate, signified by correlation coefficient of 0,603%, which is at strong-level of correlation.